2017
DOI: 10.1038/srep44989
|View full text |Cite
|
Sign up to set email alerts
|

Conditional deletion of Ndufs4 in dopaminergic neurons promotes Parkinson’s disease-like non-motor symptoms without loss of dopamine neurons

Abstract: Reduction of mitochondrial complex I activity is one of the major hypotheses for dopaminergic neuron death in Parkinson’s disease. However, reduction of complex I activity in all cells or selectively in dopaminergic neurons via conditional deletion of the Ndufs4 gene, a subunit of the mitochondrial complex I, does not cause dopaminergic neuron death or motor impairment. Here, we investigated the effect of reduced complex I activity on non-motor symptoms associated with Parkinson’s disease using conditional kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 91 publications
2
32
0
Order By: Relevance
“…However, in MSN KO mice astrocytic mitochondrial function is likely spared. Finally, a recent study shows that Ndufs4 deletion in dopaminergic neurons causes Parkinson’s disease-like non-motor symptoms without neuronal loss, likely due to reduced dopamine brain levels (Choi et al, 2017 ). Hence, it is feasible that even though not sufficient to elicit neurodegeneration, lack of Ndufs4 may alter MSN function leading to behavioral deficits.…”
Section: Discussionmentioning
confidence: 99%
“…However, in MSN KO mice astrocytic mitochondrial function is likely spared. Finally, a recent study shows that Ndufs4 deletion in dopaminergic neurons causes Parkinson’s disease-like non-motor symptoms without neuronal loss, likely due to reduced dopamine brain levels (Choi et al, 2017 ). Hence, it is feasible that even though not sufficient to elicit neurodegeneration, lack of Ndufs4 may alter MSN function leading to behavioral deficits.…”
Section: Discussionmentioning
confidence: 99%
“…However, drugs that effectively blunt the toxicity of these compounds have consistently failed in human clinical trials [ 249 , 250 , 251 ]. An influential paper on this topic demonstrated that impairing complex I function in DAergic neurons by deleting one of its subunits (Ndufs4) had little effect on them and did not alter the sensitivity to toxins like rotenone [ 252 , 253 , 254 , 255 ]. That said, making complex I insensitive to rotenone or MPTP by knocking down p13 confers neuroprotection in toxin models of PD [ 256 ].…”
Section: Is Mitochondrial Dysfunction Sufficient To Cause Pd?mentioning
confidence: 99%
“…In fact, the NADH dehydrogenase (ubiquinone) 1 alpha subcomplex, assembly factor 1 ( Ndufaf1 ) gene was found to be located in the interval of the anx gene and was downregulated in the anx/anx mice. Aside from these two models, one can find mentioned in the literature food provided ad libitum to facilitate the nutrition of weak animals, such as Ndufs4 −/− mice ( Alam et al, 2015 ; Choi et al, 2017 ; Karamanlidis et al, 2013 ; Kruse et al, 2008 ; Quintana et al, 2010 , 2012 ).…”
Section: Discussionmentioning
confidence: 99%